Developing Smart City: Based on the Assessment of Smart Projects in Medium-Size Cities, Vietnam - Hoàng, Việt Bách Khoa (2022)
Nowadays, the process of urbanization in Vietnam took place at a relatively high speed compared to the other regions. However, the process of urbanization is also facing many difficulties, almost urban must be concerned with well-managed, urban planning and construction work. when the industrial revolution 4.0 is booming, the successful construction of a smart city model will be able to create a breakthrough solution in solving problems. In recent years, the application of smart mobile devices has been introduced into Vietnam and thrived in many economic sectors, smart technology has crept into the fields of telecommunications, banking, e-commerce, payment and communication. Although majority cities in Vietnam, which not yet capable of developing technology, but still a potential level of understanding and correct orientation on the ICT driven adapted with reference to smart city concept. This study assessed the model of dimension issues on approach, paradigm, and source of capital which play the most important role in building smart city then case study was analyzed through 3 cities’ smart projects Bac Ninh, Da Lat, Nha Trang. While Bac Ninh and Nha Trang city has specific directions and strategies based on the city's SWOT assessments, Da Lat city has not yet achieved some basic requirements for conducting construction steps of smart city. This research contributes a perspective to find the adaptive direction for decision-making on smart city developing in medium-size cities of Vietnam.